Analysis of Factors Affecting the Delay in The Publication of Financial Statements (A Case Study of Companies Listed on The Indonesia Stock Exchange) - Betaria Sonata; Tri Joko Prasetyo; Usep Syaipudin (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2026)
This study investigates the effect of liquidity, leverage, profitability, and financial distress on financial statement publication delay among property and real estate companies listed on the Bursa Efek Indonesia during 2017-2024. Using a quantitative approach with pooled cross-sectional secondary data, the study applies binary logistic regression analysis. Publication delay is measured using a dummy variable, while liquidity, leverage, and profitability are proxied by the Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA), respectively. Financial distress is measured using the Zmijewski Model. The results indicate that liquidity has a negative and significant effect on publication delay, implying that companies with stronger liquidity tend to report more timely. Leverage shows a negative but insignificant effect, while profitability and financial distress exhibit positive and insignificant effects. These findings highlight liquidity as the primary determinant of reporting timeliness, whereas leverage, profitability, and financial distress do not significantly influence publication delay within the observed sample.